Meta Analisis Pengaruh Model Pembelajaran Kooperatif Tipe Student Team Achievement Division (STAD) pada Mata Pelajaran Fisika terhadap Hasil Belajar Siswa - Firmansyah Simanjuntak; Angin Jonatan A. D. P. Sinaga; Sumardi Rivandi Sitohang (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
Inappropriate learning models and lack of student interest and attention to physics learning result in unsatisfactory learning outcomes. The purpose of the study was to determine how the effect of Cooperative Learning model type Student Team Achievement Division (STAD) on student learning outcomes. The research method used is meta-analysis, data collection for this research by reviewing and browsing online articles. The results of the study found that the Student Team Achievement Division (STAD) type Cooperative learning model obtained an overall average effect size of 1.61, which means that the STAD type Cooperative learning model can influence student learning outcomes in Physics subjects. Learning material that is very influential in the application of the STAD type is Circular Motion as seen from the effect size value which is in the high category with a value of 8.81. The grade level that obtained a high category in applying the Student Team Achievement Division (STAD) type learning model was SMK class X with an effect size value of 2.2.